USE OF ARROWROOT IN DENTISTRY- A REVIEW - Francis, Twinkle; Somasundaram, Jayalakshmi; A.K , Anjali (International Journal of Psychosocial Rehabilitation, 2020)
Arrowroot is a source of unconventional starch that is known to have various therapeutic benefits. Maranta arundinacea, or arrowroot, possesses various chemical components such as alkaloids, glycosides, phenolic compounds, saponins, phenols, phosphorus, sodium, potassium, magnesium, iron, calcium, and vitamin B that help in improving circulation and metabolism. It is famously used as a traditional remedy for athlete’s foot skin infection, UTIs, and diarrhea as well. The potential of arrowroot has not been fully utilized, mainly due to a lack of knowledge on its technological and functional properties. Several studies have shown that these properties make it ideally suited to treating oral pain, including gingivitis. It also has anti-inflammatory properties that could be used to cure a range of inflammatory diseases of the oral cavity. It is well known and said to be administered by boiling in water or seasoned with milk. It is said to cure patients with irritable bowel syndrome. Some studies also reveal that it decreases cholera-induced net water secretion; by reviewing various articles, this study may be helpful in determining the efficiency of properties of a natural substance when introduced with the help of nanotechnology. The relevant articles used for this study were collected from the years 2000-2019. In the future, nanotechnology can develop dose-dependent formulations consisting of arrowroot as the major component and associate it with other compounds to target gingival inflammation and other periodontal problems.